The painter and the poet: Olavo Bilac as a translator of children's illustrated stories - Pomari, Gerson Luís (Revista de Letras, 2009)
This article analyzes the translation, made by Olavo Bilac (1865-1918), of the German writer Wilhelm Busch’s Max und Moritz - Eine Bubengeschichte in sieben Streichen. Combining rhymed and measured verses to illustrations and forming narrative sequences, Busch developed a means of expression which may be defined as illustrated story, a predecessor form of the current comics. To the translator of this kind of text, the biggest challenge is in comprehending the relationship between the two languages which compose the text - words and images.